Eco-Art therapy: Group guidance techniques for recognizing students’ emotions - Kulsum, Siti; Siregar, Ilham Khairi (Universitas Islam Negeri Raden Intan Lampung, 2022)
Eco-art therapy as a creative and innovative approach can be applied in guidance and counseling. The aim of this study was to the implementation of eco-art therapy in group guidance. This study used was comparative descriptive research. The participants involved consisted of four counselees at SMA Negeri 2 Bandung. The data collection instruments used in this study were observation and interviews which were analyzed using the data triangulation method and it was undertaken by reducing, presenting and verifying so that conclusions could be gotten. The results of the analysis showed that group guidance could encourage counselees to share experiences and express their emotions, be able to identify and understand needs so that they can make decisions in accordance to their needs independently through objects composed of natural materials. The implementation of eco-art therapy in group guidance provided information for guidance and counseling teachers to provide stimulants that could stimulate counselees to solve problems independently.